Application of Business Model Canvas for Solar Thermal Air Conditioners - Kalair, Ali Raza; Dilshad, Saad; Abas, Naeem; Seyedmahmoudian, Mehdi; Stojcevski, Alex; Koh, Kek (Frontiers in Energy Research, 2021)
Growing population, burgeoning economies, and technology-driven lifestyles demand more supply of energy. Existing energy supply pattern primarily depends on fossil fuels that have initiated climate change provoking myriad problems. Integration of renewable energy sources in the existing energy supply system is a complex and challenging task keeping in view the depleting fossil fuels and prevailed environmental challenges Existing cold storage farms are working on traditional compressors and HVAC system, causing more use of electricity. Similarly, existing data centers and supermarkets are also using conventional refrigerant. These systems also use hazardous environmental refrigerants, which make these systems more dangerous. In the summer season, comfort cooling and refrigeration requirements rise to peak in hot climate areas forcing utilities to supply more electrical energy to meet the demand. Therefore, a solar thermal cooling system employing a solar absorption chiller operated through a hot water stream generated by a solar evacuated glass tube collector with CO2 as refrigerant is simulated in the TRNSYS ® Simulation environment. The results are generated for the hot clime of Multan, Pakistan and the average obtained temperatures of the three rooms; cold storage room, office and Kitchen were 18.43 °C, 26.25 °C, and 29.83 °C, respectively. However, every startup or new idea needs a proper business model before entering into the market. This paper offers a complete insight and a future perspective for the reader to develop a precise business model for commercialization of his/her project. A business model is designed for solar thermal air conditioners for domestic, cold storage and data centers applications in the world, after reviewing and interviewing manufacturers and customer segment in air conditioning fields. Data were collected through semi-structured one-to-one interviews from a convenient sample of 10 national and international respondents, and their views were thematically analyzed. The implementation of a business model using a case for the Pakistani market is presented. A business model for a solar cooling system utilizing the abundant CO2 as a refrigerant is presented in this paper. This business model is equally suitable for designing a business model for any renewable energy product in the world.